Studi Literatur: Manajemen Risiko Strategis dan Reputasi Dalam Keberlanjutan Organisasi - Jenia Silitonga; Hairunisa Astari (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
Risk management has become an important element in maintaining organizational sustainability amid competition, business environment changes, and increasing stakeholder demands. This article aims to examine the concepts, relationships, and management strategies of strategic risk and reputational risk through a literature review approach. The method used is a literature study by reviewing relevant scientific journals, articles, and academic sources published within the last ten years. The findings show that strategic risk arises from inappropriate decision-making, market changes, competition, and an organization’s failure to adapt to environmental dynamics. Meanwhile, reputational risk is associated with negative stakeholder perceptions caused by service quality issues, communication crises, ethical violations, and operational failures. This review also indicates that both risks are interrelated and need to be managed in an integrated manner so that organizations can maintain performance, trust, and long-term sustainability.